2022
DOI: 10.3390/plants11101351
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Ca2+ and Other Regulators Assists Plants in Responding to Abiotic Stress

Abstract: Plants have evolved many strategies for adaptation to extreme environments. Ca2+, acting as an important secondary messenger in plant cells, is a signaling molecule involved in plants’ response and adaptation to external stress. In plant cells, almost all kinds of abiotic stresses are able to raise cytosolic Ca2+ levels, and the spatiotemporal distribution of this molecule in distant cells suggests that Ca2+ may be a universal signal regulating different kinds of abiotic stress. Ca2+ is used to sense and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 132 publications
(136 reference statements)
0
22
0
1
Order By: Relevance
“…However, the molecular nature of initial perception of salt stress and the subsequent signal relay remain unclear [ 18 , 20 , 21 ]. Calcium is a universal secondary messenger [ 22 ]. Cytosolic free Ca 2+ rapidly increases within seconds of plant exposure to NaCl [ 16 , 21 , 23 ], implying that salt sensor(s) are tightly coupled with stress-responsive Ca 2+ channels [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular nature of initial perception of salt stress and the subsequent signal relay remain unclear [ 18 , 20 , 21 ]. Calcium is a universal secondary messenger [ 22 ]. Cytosolic free Ca 2+ rapidly increases within seconds of plant exposure to NaCl [ 16 , 21 , 23 ], implying that salt sensor(s) are tightly coupled with stress-responsive Ca 2+ channels [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multiplicity of stimuli that can trigger Ca 2+ transients as a common second messenger [ 22 ], together with the fact that Ca 2+ is an essential macronutrient, prompts the question of how Ca 2+ signaling can achieve output specificity [ 28 ]. Ca 2+ transients can be further imbricated with and shaped by concurrent signals of different nature that assist signal decoding and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium signals have been shown to be involved in early plant defence sensing, and response to salt and drought stress ( Knight et al., 1997 ; Kiegle et al., 2000 ; Li et al., 2022 ). Prior studies tracked Ca 2+ signals utilising various green fluorescent sensors including R-GECO1 ( Stanley et al., 2018 ), YCNano-65 ( Choi et al., 2014 ) and MatryoshCaMP6s ( Ast et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a second messenger, Ca 2+ plays an important role in intracellular signaling pathways of acclimation to heavy metals and other stressors. Ca 2+ enters the cytoplasm through cyclic nucleotide-gated calcium channels (CNGCs) and interacts with calcium-binding proteins, including calcium-dependent protein kinase (CDPK), calmodulin (CaM), and calmodulin-binding protein kinase ( Li Y. Q. et al., 2022 ). Of these, CDPKs are involved in phosphorylating NADPH oxidase to produce ROS ( Li Y. Q. et al., 2022 ), whereas the Ca 2+ /CaMs complex promotes NO synthase activity to produce NO ( He et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ enters the cytoplasm through cyclic nucleotide-gated calcium channels (CNGCs) and interacts with calcium-binding proteins, including calcium-dependent protein kinase (CDPK), calmodulin (CaM), and calmodulin-binding protein kinase ( Li Y. Q. et al., 2022 ). Of these, CDPKs are involved in phosphorylating NADPH oxidase to produce ROS ( Li Y. Q. et al., 2022 ), whereas the Ca 2+ /CaMs complex promotes NO synthase activity to produce NO ( He et al., 2015 ). Here, we observed that Cd induced CNGC activity, along with Ca 2+ -related ROS and NO production, in D. pinnata roots ( Supplementary Figure S9 ).…”
Section: Discussionmentioning
confidence: 99%